Training and Identity in a Collaborative Program. - Major, Patricia (2003)
Keywords: dept.sed; faculty_collection; sabbatical_report

Teachers’ acquisition of knowledge about English word structure - Spear-Swerling, Louise; Brucker, Pamela Owen (Annals of Dyslexia, 2003)
Previous research suggests that teachers' knowledge about English word structure (e.g., the phonological structure of words and common orthographic patterns in English) may be limited, although this knowledge is important for effective teaching of word decoding. This study examined teacher education students' knowledge about word structure, and improvements in their knowledge as a result of instruction, using three tasks: graphophonemic segmentation, classification of pseudowords by syllable type, and classification of real words as phonetically regular or irregular. Participants came from a special education certification program and included both preservice and inservice teachers. Results indicated that prior preparation to teach reading influenced participants' initial performance on two of the three word-structure tasks (all but graphophonemic segmentation); however, prior experience in teaching reading did not influence word-structure knowledge. A subset of participants who received specific instruction about word structure improved their knowledge relative to a comparison group of teacher education students who did not receive word-structure instruction. Prior preparation did not influence participants' responsiveness to instruction. Conclusions support the viewpoint that teacher education must include information about English word structure for educators who will teach reading and suggest that sufficiently intensive instruction may be important in developing word-structure knowledge.
Keywords: dept.sed